Adaptation of Translational Machinery in Malaria Parasites to Accommodate Translation of Poly-Adenosine Stretches Throughout Its Life Cycle - Erath, Jessey; Djuranovic, Sergej; Djuranovic, Slavica Pavlovic (Frontiers in Microbiology, 2019)
Malaria is caused by unicellular apicomplexan parasites of the genus Plasmodium, which includes the major human parasite Plasmodium falciparum. The complex cycle of the malaria parasite in both mosquito and human hosts has been studied extensively. There is tight control of gene expression in each developmental stage, and at every level of gene synthesis: from RNA transcription, to its subsequent translation, and finally post-translational modifications of the resulting protein. Whole-genome sequencing of P. falciparum has laid the foundation for significant biological advances by revealing surprising genomic information. The P. falciparum genome is extremely AT-rich (~80%), with a substantial portion of genes encoding intragenic polyadenosine (polyA) tracks being expressed throughout the entire parasite life cycle. In most eukaryotes, intragenic polyA runs act as negative regulators of gene expression. Recent studies have shown that translation of mRNAs containing 12 or more consecutive adenosines results in ribosomal stalling and frameshifting; activating mRNA surveillance mechanisms. In contrast, P. falciparum translational machinery can efficiently and accurately translate polyA tracks without activating mRNA surveillance pathways. This unique feature of P. falciparum raises interesting questions: 1) How is P. falciparum able to efficiently and correctly translate polyA track transcripts, and 2) What are the specifics of the translational machinery and mRNA surveillance mechanisms that separate P. falciparum from other organisms? In this review, we analyze possible evolutionary shifts in P. falciparum protein synthesis machinery which allow efficient translation of an AU rich-transcriptome. We focus on physiological and structural differences of P. falciparum stage specific ribosomes, ribosome-associated proteins, and changes in mRNA surveillance mechanisms throughout the complete parasite life cycle, with an emphasis on the mosquito and liver stages.